Aspectos morfofisiológicos e nutricionais das forrageiras Mombaça e Marandu na Amazônia em sistema silvipastoril - Oliveira, Leonardo Bernardes Taverny (Universidade Federal do Tocantins, 2016)
The objective of the present work to check the power of adaptation of Panicum maximum cv. Mombasa and Urochloa brizantha (syn. Brachiaria) cv. Marandu in silvopastoral system and the most responsive variables different swings luz.O experiment was conducted at the School of Veterinary Medicine and Animal Science of the Federal University of Tocantins were evaluated two forage species Panicum maximum cv. Mombasa and Brachiaria brizantha cv. Marandu under three shading levels (0, 25 and 50%). In the leaf blade was measured the thickness of the parenchyma tissue (mesophyll), components of the vascular bundle (metaxylem and metafloema), the vascular bundle sheath, abaxial epidermis and adaxial, bulliform cells, sclerenchymatic sheath sclerenchymatic cap, sclerenchymatic extension, length of chloroplasts and secondary thickening of the epidermis; chlorophylls a, b, and total carotenoid; Ca2 +, Mg2 +, P, K + and N was used multivariate method Principal Component Analysis to select the most responsive variables and the discrimination of species to be used in the test medium. The forage better response to natural shading, was Mombasa grass which had its adaptive ability translated into essential to their survival and production, as thick mesophyll which was higher than in Marandu in 25% shading (40 and 27 respectively) ; the chlorophyll a: b also showed similar response, (1.32 and 1.03), an increase in the proportion of chlorophyll b. The lower sensitivity of Mombasa to shading in relation to Marandu resulted in a higher proportion of sclerenchyma that has low degradability resulting in lower production of gas.